Konsep Percaya Diri Dalam Al Qur’an Dan Implikasinya Terhadap Kehidupan Manusia - Suhaili, Achmad (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2019)
Self-confidence is an aspect of the human personality that functions important to actualize its potential. Without self-confidence, many problems will arise in humans. With the presence of confidence, someone will get along easily. Facing people who are older, smarter and richer, they are not ashamed to be awkward. They will dare to show themselves as they are, without prominently-highlighting excesses and covering up shortcomings. This is because people who are confident have truly understood and trusted their condition, so that they have been able to accept their condition as they are. Does the Qur'an talk about the concept of self-confidence? And how does the Qur'an talk about the concept of self-confidence? Of course there is no verse of the Qur'an that speaks of self-confidence lexically "al tsiqah bi al nafs" translation from confidence. However, there are many verses of the Qur'an that talk about human concepts according to the Qur'an and calls to believe in their ability to change, never be afraid and worried, do not be anxious and so on that need to be assessed thematically. According to Izzatul Jannah, the higher a person's faith, the higher the level of confidence. In the Qur'an it is stated that self-confidence in the form of a comfortable feeling of peace, without feeling sad, afraid and worried will come to those who believe in Allah swt. "Those who say:" Our Lord is God "then they affirm their position, the angels will come down to them (by saying): "Do not be afraid and do not feel sad; and delight in (obtaining) the heaven that God has promised you "(Fusshilat: 30) Confidence in the Qur'an starts from a noble conception of mankind, namely the Khalifah of Allah, the best of creatures, and creatures that are free of will. The concept of self-confidence in the Qur'an begins with having a Self Concept (Ma’rofatun Nafsi), Positive Thinking, Faith and Charity, Tawakalkepada Allah, Gratitude, and Muhasabah (Self Evaluation).